Palynomorph assemblages, palynofacies, depositional environments and Paleogene syn-rift sedimentary sequences in the Enreca-3 - Quang, Chu Duc (Petrovietnam Journal, 2014)
The article presents the results of analyses of the palynomorph assemblages and depositional environments in the Enreca-3 well in the South East of Bach Long Vi island. At the same time, the author also sets up and compares subdividing sequences by bio-stratigraphy and CycloLog analysis. The study results indicate that encountered sediments in the Enreca-3 well were deposited in the fresh water deep lacustrine environment in the late Oligocene. These sediments have the same age as Tra Tan formation in the Cuu Long basin.